Diabetes alters immune response patterns to acute melioidosis in humans. Issue 7 (8th May 2019) - Kronsteiner, Barbara; Chaichana, Panjaporn; Sumonwiriya, Manutsanun; Jenjaroen, Kemajitra; Chowdhury, Fazle Rabbi; Chumseng, Suchintana; Teparrukkul, Prapit; Limmathurotsakul, Direk; Day, Nicholas P.J.; Klenerman, Paul; Dunachie, Susanna J.
Abstract: Diabetes mellitus (DM) is a serious global health problem currently affecting over 450 million people worldwide. Defining its interaction with major global infections is an international public health priority. Melioidosis is caused by Burkholderia pseudomallei, an exemplar pathogen for studying intracellular bacterial infection in the context of DM due to the 12‐fold increased risk in this group. We characterized immune correlates of survival in peripheral blood of acute melioidosis patients with and without DM and highlight different immune response patterns. We demonstrate the importance of circulating NK cells and show that CX3CR1 expression on lymphocytes is a novel correlate of survival from acute melioidosis. Furthermore, excessive serum levels of IL‐15 and IL‐18BP contribute to poor outcome independent of DM comorbidity. CD8 + T cells and granzyme B expression in NK cells are important for survival of non‐DM patients, whereas high antibody titers against B. pseudomallei and double‐negative T cells are linked to survival of DM patients. Recall responses support a role of γδ T‐cell‐derived IFN‐γ in the establishment of protective immunity in the DM group. Defining the hallmarks of protection in people with DM is crucial for the design of new therapies and vaccines targeting this rapidly expanding risk group. Abstract : NK cells and low levels of IL‐15, IL‐18, and IL‐18BPa are determinants of survival from acute melioidosis. Patients without DM (non‐DM) rely on CD8 + T cells, CX3CR1 and GzmB expression on NK cells, and sufficient antigen presentation for survival, while patients with DM rely on antibodies and double‐negative T cells.